Narrating selves: Alterity and Simultaneity In Lutanga Shaba’s Secret of a Woman’s Soul, Peter Godwin’s Mukiwa: A White Boy In Africa, Nelson Mandela’s Long Walk To Freedom And Barack Obama’s Dreams From My Father - Moyo, Tafara (Midlands State University, 2017)
This study is an analysis of auto-biographical narratives reinterpreted as auto-heterobiography to open space to an exploration and interrogation of alterity. Analysis of these narratives operated via postmodernist, postcolonial and philosophical discourses.The problem of narrating traumatized, political and hybrid or cosmopolitan selves was sited as resident in the primordial polytropos of the human experience which exposes narratives as aporetic and incomplete once postured as closed or as metanarratives.This study concluded that narratives ultimately assume a paradoxical stance which neither opposes nor accedes to auto-heterobiographical narratives as possible or impossible.The narratives analysed posed the human experience as marked by ambiguity, heteroglossia, polyphony and ambivalence, thus compelling the conclusion that no experience is knowable via a single version of narration.This study posed alterity as both an affirmation and a question of the question of originary, unified and coherent selves.